Leontopodium nyingchiense (Asteraceae), a new species from Xizang (Tibet), China - Wen-Qi He; Fang-Yu Zhao; Zhao-Fu Chu; Guo-Zhu Chai; Kai-Hui Zhao; Jing-Qin Tian; Bao-Xin Zhang; Fang-Yuan Zhang; Zhi-Hua Liao; Wei-Lie Zheng; Xiao-Zhong Lan (PhytoKeys)
Leontopodium nyingchiense, a new species of Asteraceae from the Xizang (Tibet) Autonomous Region of China, is described and illustrated here. Morphologically, it is most similar to L. lingianum but can be distinguished by the combination of monoecious and dioecious individuals, involucral bracts arranged in 3–5 series (with outer series herbaceous and middle to inner series membranous), fimbriate apices on female florets, rough-edged lobes on male florets, and achenes lacking costae. Phylogenetic analyses further support the separation of this new species from related taxa. Finally, we characterize this new species through both morphological comparisons and molecular analyses.